2017
DOI: 10.31234/osf.io/ar6kq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rational metareasoning and the plasticity of cognitive control

Abstract: The human brain has the impressive capacity to adapt how it processes information to highlevel goals. While it is known that these cognitive control skills are malleable and can be improved through training, the underlying plasticity mechanisms are not well understood. Here, we develop and evaluate a model of how people learn when to exert cognitive control, which controlled process to use, and how much effort to exert. We derive this model from a general theory according to which the function of cognitive con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

6
0

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 56 publications
(103 reference statements)
7
26
0
Order By: Relevance
“…As shown in Figure S1, the EVC model is able to reproduce 266 these classic observations, as well as the more basic observation that performance worsens 267 (slower and less accurate responding) on incongruent relative to congruent trials ( given performance-contingent reward (e.g., money or positive social feedback for completing a 280 task) than agents that anticipated lower rewards (Figure 2A). Consistent with analogous 281 simulations reported in previous work (Lieder et al, 2018;Musslick et al, 2015), we found that 282 increasing anticipatory affect predicts increased control allocation for equivalent rewards. As a 283 result, compared to agents that anticipated low rewards, agents that anticipated high rewards 284…”
supporting
confidence: 87%
See 1 more Smart Citation
“…As shown in Figure S1, the EVC model is able to reproduce 266 these classic observations, as well as the more basic observation that performance worsens 267 (slower and less accurate responding) on incongruent relative to congruent trials ( given performance-contingent reward (e.g., money or positive social feedback for completing a 280 task) than agents that anticipated lower rewards (Figure 2A). Consistent with analogous 281 simulations reported in previous work (Lieder et al, 2018;Musslick et al, 2015), we found that 282 increasing anticipatory affect predicts increased control allocation for equivalent rewards. As a 283 result, compared to agents that anticipated low rewards, agents that anticipated high rewards 284…”
supporting
confidence: 87%
“…directing information processing (Dreisbach & Fischer, 2012;Dreisbach & Fröber, 2018;Inzlicht 358 et al, 2015), normative theories of cognitive control have largely overlooked affect's role in 359 control allocation. In this study, we leveraged a computational implementation of the EVC theory 360 (Lieder et al, 2018;Musslick et al, 2015;Shenhav et al, 2013) to simulate several candidate 361 mechanisms through which cognitive control can be influenced by integral affect (e.g., 362…”
Section: Figure 5 Effects Of Control Costs On the Expected Value Of mentioning
confidence: 99%
“…One of the main advantages of the theory is its ability to integrate a wide range of behavioral and neural findings. The computational implementation of the theory has been shown to account for various effects associated with the allocation of cognitive control such as the sequential adaptation effects and post-error slowing (Musslick et al, 2015), including how individuals can learn about features of their environment that predict incentives for and demands of control allocation (Lieder et al, 2018).…”
Section: Computational Models Of Cognitive Controlmentioning
confidence: 99%
“…After the original formulation of the EVC theory (Shenhav et al, 2013), the more recent work has developed a computational implementation of the theory (Lieder et al, 2018;Musslick et al, 2015). In the computational implementation, performance of each task (e.g., responding to the color or to the word of a Stroop stimulus) is implemented as a process of evidence accumulation toward a decision boundary.…”
Section: Simulation-based Behavioral Predictionsmentioning
confidence: 99%
See 1 more Smart Citation